Abu Hanifah's Perspectives on the Bai’ as-Salam Contract and Its Significance in Contemporary Online Buying and Selling Transactions - M. Nanang Febrianto; Muhamad Aqim Adlan; Muhammad Aswad (Institut Agama Islam Negeri Lhokseumawe, 2024)
The purpose of the study is to explain the Islamic economic thought of Abu Hanifah on the Bai' As-Salam contract in online buying and selling transactions in the marketplace. The analysis method is carried out qualitatively with literature studies, data is collected through books, journals, or publications relevant to the problem. The study results show that Abu Hanifah was an Islamic thinker during the Umayyad Dynasty. Abu Hanifah's Islamic economic thought, namely the Bai' As-Salam Contract, aims to minimize disputes between sellers and buyers by setting detailed and clear conditions in the contract such as price, time, place of delivery, quality, type of commodity, quality, and quantity. In practice, the Bai' As-Salam contract in Indonesia is permitted based on the Fatwa of the National Sharia Council of the Indonesian Ulema Council in 2000 concerning the sale and purchase of salam based on the Qur'an, Hadith and Ijma'. The Bai' As-Salam contract carried out online and offline is halal and permitted as long as there aren’t elements of usury, monopoly, injustice, and fraud. Meanwhile, payments via Cash on Delivery and E-Wallet Fiqh muamalah as long as it doesn’t conflict with Islamic law.